Bioactive Polysaccharides in Byproducts from Seaweed Production and Addition of the Bioactive Polysaccharide Fucoidan to Skin Care - Ingibjörg Ásbjörnsdóttir 1994- (2019)
The sulfated polysaccharide fucoidan, found in many brown seaweeds, has great potential in pharmaceuticals, nutraceuticals, functional foods and cosmeceuticals. Fucoidans have been studied widely and have been isolated from different species due to their varied biological activities, including antivirus, antitumor, anti-inflammatory and antioxidant function. Even though this polysaccharide has been studied widely there still isn’t much knowledge about its chemical composition and how it differs between species. The aim of this study was two-fold. (1) To isolate fucoidans from byproducts of two species of brown seaweeds, Ascophyllum nodosum and Fucus vesiculosus and optimize an extraction method using two types of 0.1 M acids (HCl and H2SO4) and four temperatures (30°C, 37°C, 50°C, and 60°C). To get a better picture of the characteristics of the byproducts of these two species and the efficacy of each extraction method, carbohydrate measurements and polyphenol measurements were also performed. And (2) to isolate fucoidans from two species of brown seaweeds, Saccharina latissima and Alaria esculenta and test these fucoidans extracts in skin care from Una Skincare. Their stability was tested with accelerated stability test over two-month time period. Large amount of underutilized, valuable brown seaweeds is found all around the coasts of Iceland and the purpose of this study was to further utilize these raw materials, both from unprocessed seaweeds as well as byproducts of seaweed processing. The results indicated that byproducts from seaweed processing of A. nodosum and F. vesiculosus had different characteristics and different extraction conditions gave different yields. Byproducts from both species contained high molecular weight polysaccharides, as well as smaller carbohydrates. The fucose content in byproducts of F. vesiculosus was found higher than in A. nodosum, and it was therefore estimated that byproducts of F. vesiculosus contained higher amount of fucoidans. The most effective extraction conditions for ...